PENGARUH FISIOLOGIS SAPI PERAH PADA KONDISI LINGKUNGAN TERKONTROL - M. Rizki Amin Badali; Muhammad Rizal; Muhammad Riyadhi; Ika Sumantri (www.ulm.ac.id, 2023)
This research aims to determine the physiological responses of FH crossbred dairy cows kept in acontrolled microclimate barn in a tropical lowland area. Eight (8) FH crossbred cows were subjectedto two (2) treatments with 42 repetitions each, which were housed in a controlled microclimate barn.The FH crossbred cows were housed without any cooling equipment, such as sprinklers and fans (a),and then with cooling equipment, including sprinklers and fans (b), each for one (1) week. Theobserved parameters were barn temperature, body temperature, and respiratory rate in the morning(06.00), afternoon (13.00), and evening (17.00). The data were analyzed using a statistical sample Ttest with the help of SPSS. The results of the data analysis showed that the barn temperature intreatments (a) and (b) in the morning was 26±0.81 and 25.25±0.95oC, respectively, and there was nosignificant difference statistically (P>0.05). However, the barn temperature in the afternoon fortreatments (a) and (b) was (33.5±0.57 and 30.25±1.70oC), respectively, and there was a significantdifference statistically (P<0.05). Similarly, the barn temperature in the evening for treatments (a) and(b) was (32±0.81 and 29.25±1.5 oC), respectively, and there was a significant difference statistically(P<0.05). Regarding the physiological responses of FH crossbred cows, the body temperature in themorning for treatments (a) and (b) was (37.66±0.45 and 37.21±0.47oC), respectively. The bodytemperature in the afternoon was (38.15±0.50 and 37.39±0.73oC), respectively, and in the eveningwas (38.07±0.48 and 37.43±0.45oC), respectively. There was a significant difference statistically (P<0.05) in all three time periods. As for the respiratory rate, in the morning, there was no significantdifference statistically (P>0.05) between treatments (a) and (b), with rates of (33.71±5.82 and33.28±7.78 breaths/minute), respectively. However, in the afternoon, the respiratory rate fortreatments (a) and (b) was (57.96±13.31 and 43.75±14.07 breaths/minute), respectively, and in theevening, it was (50.89±9.30 and 42.82±8.39), respectively. There was a significant differencestatistically (P<0.05) for both afternoon and evening periods. Based on the research results, it can beconcluded that the controlled microclimate barn conditions have an impact on the physiologicalresponses of FH crossbred cows in the tropical lowland area.